Application of Matrix Scoring Techniques to evaluate marine debris sources in the remote islands of the Azores Archipelago. (June 2019) - Pieper, Catharina; Amaral-Zettler, Linda; Law, Kara Lavender; Loureiro, Clara Magalhães; Martins, Ana
Abstract: Three-quarters of all marine debris (MD) consists of plastic, a reflection of their worldwide use, production and waste mismanagement. Data on MD distributions can improve our ability to effectively reduce debris that escapes onto shorelines and the ocean. In this study, the Matrix Scoring Technique (Marine Strategy Framework Directive Technical Group on Marine Litter) was applied as an approach to calculate the likelihood of single debris items originating from a series of potential sources. Factors considered were: identity and function of debris, beach location, influential activities, "mix" of debris found, presence of indicator items, and quantity of MD. The standing-stock (abundance and composition) of MD was investigated in two sandy beaches (Conceição and Porto Pim) of the Azores Archipelago (NE Atlantic) for the period 2012–2018. The results of this study show promise towards the implementation of a new classification method to determine beach debris sources in remote open-ocean areas. Graphical abstract: Image 1038380 Highlights: First in-depth assessment of potential marine debris sources in the Azores region. Trends of debris sources in this study diverge from other source-oriented studies. Implementation of such techniques nurture new forms of local waste management. Abstract : The application of source-targeting tools in open ocean remote areas such as the Azores, adds important information on land/or ocean-based sources, while providing the means to readapt waste management actions at local basis.